2019
DOI: 10.1128/aem.02788-18
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Functional Analysis of the Type IV Pilus Gene Cluster in Streptococcus sanguinis SK36

Abstract: Streptococcus sanguinis, dominant in the oral microbiome, is the only known streptococcal species possessing a pil gene cluster for the biosynthesis of type IV pili (Tfp). Although this cluster is commonly present in the genome of S. sanguinis, most of the strains do not express Tfp-mediated twitching motility. Thus, this study was designed to investigate the biological functions encoded by the cluster in the twitching-negative strain S. sanguinis SK36. We found that the cluster was transcribed as an operon, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Many of these genes were differentially expressed ( Supplementary Figure S6), which may be due to the intertwined nature of amino acid and carbohydrate metabolism (Radin et al, 2016). We also observed decreased expression of large, contiguous loci encoding ethanolamine utilization (Fox et al, 2009;Kaval and Garsin, 2018;Kaval et al, 2019), a type IV pilus system (Chen et al, 2019), and CRISPR-associated proteins (Makarova et al, 2015;Gong et al, 2020; Supplementary Figure S7), which are all also tied to CcpA-regulation (Bai et al, 2019).…”
Section: (Supplementarymentioning
confidence: 83%
“…Many of these genes were differentially expressed ( Supplementary Figure S6), which may be due to the intertwined nature of amino acid and carbohydrate metabolism (Radin et al, 2016). We also observed decreased expression of large, contiguous loci encoding ethanolamine utilization (Fox et al, 2009;Kaval and Garsin, 2018;Kaval et al, 2019), a type IV pilus system (Chen et al, 2019), and CRISPR-associated proteins (Makarova et al, 2015;Gong et al, 2020; Supplementary Figure S7), which are all also tied to CcpA-regulation (Bai et al, 2019).…”
Section: (Supplementarymentioning
confidence: 83%
“…S6). S. sanguinis is unusual in that it is the only streptococcal species to encode a gene cluster for the biosynthesis of a type IV pilus system (T4P) (Gurung et al, 2016) that is distinct from the T4P competence pilus (Sheppard et al, 2020), and yet few strains exhibit the twitching motility normally mediated by T4P (Chen et al, 2019). In SK36, T4P appears to be important for adherence to host cells and may be regulated by CcpA, despite the lack of a cre site in the promoter region (Bai et al, 2019;Chen et al, 2019).…”
Section: Other Findingsmentioning
confidence: 99%
“…S. sanguinis is unusual in that it is the only streptococcal species to encode a gene cluster for the biosynthesis of a type IV pilus system (T4P) (Gurung et al, 2016) that is distinct from the T4P competence pilus (Sheppard et al, 2020), and yet few strains exhibit the twitching motility normally mediated by T4P (Chen et al, 2019). In SK36, T4P appears to be important for adherence to host cells and may be regulated by CcpA, despite the lack of a cre site in the promoter region (Bai et al, 2019;Chen et al, 2019). In S. pneumoniae, the SsaR ortholog, PsaR, negatively regulates the expression of type I pilus genes in the presence of Mn (Johnston et al, 2006) whereas a Δ mntE mutant containing excess intracellular Mn showed increased expression of the same genes (Rosch et al, 2009).…”
Section: Other Findingsmentioning
confidence: 99%
“…Initial bioinformatics analyses identified five putative pilin genes located in the C. bescii T4P locus ( Table 1). Pathogenic Firmicutes, such as Streptococcus sanguinis (47,48) and C. perfringens (28), also encode for multiple pilins in their respective T4P loci, and a hypervirulent C. difficile strain encodes for as many as nine pilins distributed across five genomic loci (30). Additionally, based on amino acid 295 sequence homology, concatenated C. bescii pilin sequences clusters with other T4P loci from the majority of strongly cellulolytic Caldicellulosiruptor species (Fig.…”
Section: Discussionmentioning
confidence: 99%